GHZ phononic band-gapcrystals: fabrication, characterization and modeling - Rakhymzhanov, A.; Utegulov, Z.N.; Guney, D.; Veres, I.A. (Nazarbayev University, 2013)
Phononic band-gap crystals (PBGCs) are acoustic analogues of photonic band-gap crystals. PBGC is a composite structure possessing periodic variations of sound velocities and mass densities with high acoustic impedance contrast among its constituents, which results in band gaps stopping acoustic waves within certain frequency range due to their total reflection within this synthetic material. By pushing down structural periodicity of PBGCs into hundreds of nanometers or less one can effectively design hypersonic PBGCs to control the propagation acoustic waves with frequencies higher than 1 GHz with an ultimate goal to control heat transport at sub-micron- and nanometer scales. PBGCs can also find their applications in radio-frequency mobile communication devices and global positioning systems. Femtosecond laser-induced two-photon polymerization (FLITPP) has proved to be a viable fabrication technique to produce periodic synthetic crystals with submicron periodicity. The field of GHz phononics is just emerging, and at this point it is important to explore the actual physics that governs the behavior of these materials, as well as to hypothesize about applications
Keywords: first research week; Phononic band-gap crystals; innovative scientific research